2018
DOI: 10.1590/2179-8087.055916
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Input via Incident Rainfall in a Eucalyptus dunnii Stand in the Pampa biome

Abstract: We evaluated the nutrient input via incident rainfall in a Eucalyptus dunnii stand in the Brazilian Pampa biome. During the two-year study, we analyzed nutrient concentrations in incident rainfall (P), throughfall via drip (Pi), and stemflow (Et

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 23 publications
1
13
1
Order By: Relevance
“…In the present study, there were higher amounts of Cland SO 4 2in rainfall compared to the studies by Heartsill-Scalley et al (2007) in Puerto Rico, Dick et al (2018) in Brazil (Pampa biome), and Ashagrie & Zech (2010) in Ethiopia. The dissolved ions in rainwater will be incorporated into the soil and excess nitrate (Wamelink et al, 2009), chloride, and sulfate may impair the development of vegetation (soybean, corn, pasture, trees, among other types of soil cover) by causing toxic effects and slowing growth (Vet et al, 2014).…”
Section: Increased Concentrations Of Socontrasting
confidence: 66%
See 1 more Smart Citation
“…In the present study, there were higher amounts of Cland SO 4 2in rainfall compared to the studies by Heartsill-Scalley et al (2007) in Puerto Rico, Dick et al (2018) in Brazil (Pampa biome), and Ashagrie & Zech (2010) in Ethiopia. The dissolved ions in rainwater will be incorporated into the soil and excess nitrate (Wamelink et al, 2009), chloride, and sulfate may impair the development of vegetation (soybean, corn, pasture, trees, among other types of soil cover) by causing toxic effects and slowing growth (Vet et al, 2014).…”
Section: Increased Concentrations Of Socontrasting
confidence: 66%
“…2and Cl -, in detriment of other ions, were observed in the rainfall of the Pampa biome (Dick et al, 2018) and this has also been observed in studies from Puerto Rico (Heartsill-Scalley et al, 2007), and Congo (Laclau et al, 2003). Laclau et al (2003) identified that the predominance of SO 4 2and Clin rainwater in rural areas of Congo is dependent on the location of the study site as their study was set up 10 km from the sea and under strong influence of marine spray.…”
Section: Increased Concentrations Of Somentioning
confidence: 53%
“…Corrêa [15] found 91.6% of throughfall as function to the incident precipitation between 1.4 and 2.4 years of age. Between 4 and 6 years of age, Dick et al [16] found an average throughfall of 91.3%. In the same stand, between 7 and 8 years of age Momolli et al [11] show that the throughfall was smaller when compared to the other studies, being only 90.3%.…”
Section: Distribution Of Incident Precipitation Throughfall Stemflomentioning
confidence: 97%
“…Studying the precipitation partition the seventh to the eighth year, Momolli et al [11] concluded that 99, 90 and 52% of the throughfall, stemflow and canopy interception are explained from the incident precipitation. Monitoring carried out in Eucalyptus dunnii at different ages shows that as the age of stand increases, the percentage of throughfall decreases and the canopy interception increases [15,16,11].…”
Section: Introductionmentioning
confidence: 99%
“…Evaluating the pH in Eucalyptus dunnii stands from 5 to 6 years of age, Dick et al (2018) showed that the pH was 4.3; 5.0 and 5.3 for incident precipitation, throughfall and stemflow respectively. Correa (2011) also studying a stand of Eucalyptus dunnii from 1.4 to 2.4 years of age found the following pH values: 5.0; 5.2 and 5.3 for incident precipitation, throughfall and stemflow respectively.…”
Section: Concentration Of Ionsmentioning
confidence: 99%